Case report: Recovery from refractory myasthenic crisis to minimal symptom expression after add-on treatment with efgartigimod - Watanabe, Keiko; Ohashi, Shinichi; Watanabe, Takuya; Kakinuma, Yuki; Kinno, Ryuta (Frontiers in Neurology, 2024)
Myasthenic crisis, a life-threatening exacerbation of myasthenia gravis, is a significant clinical challenge, particularly when refractory to standard therapies. Here, we described a case of myasthenic crisis in which the patient transitioned from refractory myasthenic crisis to minimal symptom expression after receiving add-on treatment with efgartigimod, a novel neonatal Fc receptor antagonist. A 54-year-old woman who was diagnosed with anti-acetylcholine receptor antibody-positive-positive myasthenia gravis experienced respiratory failure necessitating mechanical ventilation. Despite aggressive treatment with intravenous immunoglobulins, plasmapheresis, and high-dose corticosteroids, her condition continued to deteriorate, culminating in persistent myasthenic crisis. Efgartigimod was administered as salvage therapy. Remarkable improvement in neuromuscular function was observed within days, allowing for successful weaning from mechanical ventilation. Over the subsequent weeks, the patient’s symptoms continued to ameliorate, ultimately reaching a state of minimal symptom expression. Serial assessments of her serum anti-acetylcholine receptor antibody titer showed a consistent decline in parallel with this clinical improvement. This case highlights efgartigimod’s potential as an effective therapeutic option for refractory myasthenic crisis, offering new hope for patients facing this life-threatening condition.